Growing Number of Female Senior Citizen in Old Age Homes: Challenges and Solutions - Yogi, Sheela Kumari (KMC Research Journal, 2024)
The increasing trend of the elderly population is a worldwide matter of concern. Nepal is a developing country facing challenges such as a lack of economic growth, low per capita income, poor pension system, and unemployment. These factors make life even more difficult, especially for elderly people. This study has tried to explore the growing number of old age homes for elderly people and especially the problems that elderly women face at these homes. The purpose of this study is to reveal the problems of older people, especially women, and their feelings about their safety. To complete this study several old age homes were visited and interacted with elderly people. In this course, elderly women and the members of the old age management committees were interviewed as the key informants of this study. The research concludes that the relationship between family and elderly people is getting worse due to the increasing modern lifestyle. And, as a result, elderly people are facing health and financial problems as well as security. Elderly women also have been victims of sexual abuse.